LAND USE CONFLICTS IN THE PROCESS OF LAND DEVELOPMENT APPROVAL: A REVIEW OF DECISION BETWEEN TWO LEGISLATIONS IN MALAYSIA - Suliman, Suhailizan; Samsudin, Salfarina; Ahmad, Mohd Hamdan (International Journal of Psychosocial Rehabilitation, 2020)
Land Use Planning is a process of planning to control and manage development. In Malaysia, the jurisdiction of land use planning is vested under the power of local authorities as stated under the Town and Country Planning Act 1976 (Act 172). As planning authority, Local Authority will determine the land use planning through zoning in the Local Plan. Each development proposal must be submitted to the Local Authority for approval before the development can take place. The local authority will give approval based on statutory compliance. However, there are appeal cases made by landowner concerning the rejection of Planning Permission by the Local Authority. Rejections of Planning Permission were made due to failure in obtaining approval for variation application cause by the conflict in the land condition stated in Land Title under section 52 National Land Code 1965 and and zoning in the Local Plan as enshrined under section 12 The Town and Country Planning Act 1972. Therefore, this article discussed the theoretical perspectives of development process framework with further identification of conflicts that involves two legislations. Content analysis is used to identify causes of conflict in land development process based on the provision in the National Land Code 1965 and Town and Country Planning Act 1972. The findings demonstrate that land-use conflict in land development process happens due to unclear legislative provisions application in granting development approval. The outcome of this paper can be a catalyst for comprehensive research that will provide a clear guide in determining development approval. Effective land- use conflict resolution can facilitate infrastructure development that meets people’s needs.